(untitled) (Al-Mansour Journal, 2022)
The aim of this work, focus on the problem of reducing the classification fingerprint features that has been entered to the neural network. An algorithm was introduce to work with prepared codebook to code and normalized the input samples of the back-propagation method. The main advantages of preparing codebook are the simplicity of its idea and its high speed processing. This method has been tested on the FCV2002 fingerprint database. The recognition accuracy is 94% and the equal error rate (EER) is 2.1%b...bbbbbbbbb Keyword: fingerprint recognition, codebook, backpropagation, termination ,bifurcation.